Structural evolution of poly(acrylonitrile‐co‐dimethyl itaconate) copolymer during thermal oxidative stabilization. (13th February 2015) - Fu, Zhongyu; Ma, Jianying; Deng, Yunjiao; Wu, Guangfeng; Cao, Chunlei; Zhang, Huixuan
<x xml:space="preserve">Abstract</x> The structural evolution of poly(acrylonitrile‐co‐dimethyl itaconate) [P(AN‐DMI)] copolymer was investigated by Fourier transform infrared spectroscopy (FTIR) in detail and compared with the polyacrylonitrile (PAN) homopolymer. The extent of cyclization reactions was calculated from the FTIR data. It was found that DMI comonomer had the ability to promote the cyclization reactions significantly at the temperature of 240°C, compared to the PAN homopolymer. The results of quantitative FTIR analysis in the range of 1000–1800 cm−1 showed that the DMI comonomer not only promoted the cyclization reactions, but also facilitated the oxygen uptake reactions, especially the conjugated carbonyl group in an acridone ring in the ladder polymer chains, which proved that DMI comonomer had the potential ability to make successful thermal oxidative stabilization (TOS) process. The positive effects of DMI comonomer on TOS reactions and carbon yield were further confirmed by the dynamic thermogravimetry (TG) analysis. Copyright © 2015 John Wiley & Sons, Ltd.